Effect of Aerobic Exercise on Post-Stroke Cognitive Function: A Systematic Review (2020)
Background/Aims: Literature suggests that aerobic exercise improves cognitive impairments post stroke. This systematic review was conducted to analyse evidence on the effectiveness of aerobic exercise in improving post-stroke cognitive impairments. Methods: Online databases (PubMed, EMBASE and Web of Science) were systematically searched from inception until 13 July 2017 using the keywords stroke/exercise/cognition. Clinical trials that met the inclusion criteria were assessed for methodological quality using the PEDro scale. Extracted data were synthesised for evidence. Results: A total of seven studies met the inclusion criteria. Participants in most of the studies were aged over 60 years and the majority had ischaemic stroke. The most commonly used measure for assessing cognition was the Mini Mental State Examination. The majority of studies included moderate to high intensity exercise (50–70% of VO2max) for 30–60 minutes three to five times per week. There is moderate evidence that aerobic exercise enhances global cognitive function, attention and working memory. Evidence that aerobic exercise improves memory, levels of brain-derived neurotrophic factor and executive function is conflicting and limited. Conclusions: Aerobic exercise is moderately effective in improving post-stroke cognitive impairments. More clinical trials are needed in view of the methodological limitations and paucity of existing studies.